AB1003 Is the Ultrasound Score Based on 7 Joints (US-7 SCORE) A Valid Screening Tool for Inflammatory Joint-Diseases in A Population of Volunteers? Results from the "Rheuma-Truck" Cohort. (10th June 2014) - Sewerin, P.; Vordenbäumen, S.; Brinks, R.; Liedmann, A.; Ohrndorf, S.; Backhaus, M.; Sander, O.; Kümmel, M.; Schneider, M.; Ostendorf, B.
Abstract : Objectives: To investigate the value of ultrasound (US) and the US-7 score as a screening tool in a population of volunteers visiting the "Rheuma-Truck" Methods: "Rheuma-Truck" was a mobile rheumatology office located in different city center of North Rhine Westphalia offering a screening for rheumatic diseases including Rheuma-Check questionnaire, lab-tests (MCV capillary test), imaging (US, capillaroscopy), and if positive a consultation with a rheumatologist to everybody free of charge. Ultrasound according to US-7 criteria, which is so far only evaluated as a parameter for therapy monitoring, with addition of the MCP-5 joint of the dominant hand of 605 volunteers was performed (MyLab 25 Gold, Esaote linear scanner, 15, Typ LA435). Moreover, in 236 of these volunteers the foot was assessed. Thus a total of 4102 joints were examined by ultrasound. Descriptive statistics for the patients were obtained and are reported as means ± standard deviation, ranges, frequencies or proportions as appropriate. Correlation coefficients are Pearson-correlations. Results: The mean age of the investigated cohort was 52.72 years (min. 10, max. 89 years). Sex distribution shows 72.2% females and 27.8% males. 181 (29.9%) volunteer showed inflammatory signs in ultrasound. Overall MTP-2 was using the US-7 criteria the most frequently involved joint (11.4% B-mode and/or powerdoppler) followed by the dorsal wrist (8.9%), the MCP-2 (6.6%), PIP-3 (6.0%), PIP-2 (4.3%), the ulnar wrist (3.0%), MCP-3 (2.6%), the palmar wrist (0.5%) and MTP-5 (0.4%). The additionally evaluation of the MCP-5 joint showed with 7.6% the third most pathological findings anyway. Overall 378 volunteers referred a rheumatologist because of pathological findings in Rheuma-Check, lab-tests or ultrasound. 82 of these volunteers were diagnosed as rheumatoid arthritis (13.5%). First evaluations showed high correlations between ultrasound, MCV capillary test and the Rheuma-Check questionnaire. Conclusions: Musculoskeletal ultrasound and US-7 scoring system are sufficient screening- and scoring tools for the detection of inflammatory joint alterations in a volunteer cohort. MCP-5 is a frequently involved joint in musculoskeletal ultrasound, which is not included in the US-7 scoring system yet. This study highlights the value of ultrasound in early detection of inflammatory joint diseases in a population of volunteers. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4228